Energetic and reactivity properties of 9, 10-dihydroacridine and diphenylamine: A comparative overview. (December 2017) - Freitas, Vera L.S.; Gomes, José R.B.; Liebman, Joel F.; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Gas-phase enthalpies of formation for 9, 10-dihydroacridine and diphenylamine estimated from G3(MP2)//B3LYP approach. Reactivity insights of 9, 10-dihydroacridine and diphenylamine. Benchmark values for the gas-phase enthalpies of formation of 9, 10-dihydroacridine and diphenylamine. Abstract: The purpose of this research was to determine the energetic and reactivity properties of diphenylamine and 9, 10-dihydroacridine using computational methodologies. The equilibrium geometries in the gaseous phase of the studied compounds were analysed in detail and the structural effects on the aforementioned properties were assessed. The values of the gas-phase standard molar enthalpies of formation of diphenylamine (217.7 ± 1.8) kJ·mol −1 and 9, 10-dihydroacridine (198.7 ± 4.4) kJ·mol −1 were estimated by hypothetical gas-phase reactions using the G3(MP2)//B3LYP composite method. These data were compared with the ones available in the literature, including the gas-phase enthalpy of formation of 9, 10-dihydroacridine derived from the assumption of comparability of the enthalpies of hydrogenation in the liquid and gas phases. Other gas-phase thermodynamic properties, namely the bond dissociation enthalpies (NH and CH) and the gas-phase acidities were also determined. The electrostatic potential surfaces and the frontier molecular orbitals were determined for both compounds, allowing us to infer about its reactivity. Other derived properties include the HOMO-LUMO energy gap and the ionization potential.